EVALUASI PAKAN SUPLEMEN MINYAK IKAN LEMURU DAN HIDROLISAT DARAH TERPROTEKSI BERDASARKAN KECERNAAN BAHAN KERING DAN KECERNAAN BAHAN ORGANIK DI DALAM RUMEN DAN PASCA RUMEN - Pramono, Ahmad; Kustono, Kustono; Widayati, Diah Tri; Putro, P P; Hartadi, Hari (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2016)
Increased of ruminants energy intake can be conducted by increasing the energy density of feed by using fat (oil). Protein intake can be enhanced by increasing of protected protein that escapes degradation by rumen microbes. The Aim of this research was to evaluate protected of feed supplement based on dry matter digestibility (KcBK), organic matter digestibility (KcBO) in vitro in the rumen and post-rumen. Protected feed supplement was produced from sardine fish oil and hydrolyzed blood , throught two protection methodes. It was saponification and microencapsulation. This research uses a completely randomized design with 3 treatments (feed supplements protected, soybean meal and pangola grass), which each treatment was repeated 5 times. The results in the first step (rumen) of the protected feed supplement showed that has dry matter digestibility 24.46% and organic matter digestibility 57.17%, soybean meal has dry matter digestibility 75.20% and organic matter digestibility 75.66%, and pangola grass has dry matter digestibility 50 , 81% and organic matter digestibility 59.21%. In the second step (post rumen) the digestibility of protected feed supplement has dry matter digestibility 69.04% and organic matter digestibility 66.71 72.76%, soybean meal has dry matter digestibility 90.38% and organic matter digestibility 88.23%, and the grass pangola have KcBK 63.24% and KcBO 59.21%. The results could be concluded that in the rumen protected feed supplementation is the most microbial degradation resistant compared the other and it can be degraded and digested in the abomasum to the small intestine.